(3GdJONd GdOhdi Hjf MeGjI Mbhb GdGfSGf h eHOC GdSjGOI (B: s (3OQGSI MGdJi (B: (3GdYQGb h djHjG (B/ s - (3LGSe MehO efUhQs; (3eMeO SGeM YeQh s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2021)
(3Tcd GdJONd GdOhdi dMeGjI Mbhb GdGfSGf NdGaG Hjf JjGQ eDjO h BNQ eYGQV(B: (3h CUHM GdJMQc fMh aYd GdJONd eQJHW HbhGYO GdbGfhf GdOhdi(B: (3h JJeKd Jdc GdbhGYO ai GdGJaGbjGJ GdOhdjI(B: (3GdJi CbOeJ GdOhd HGQGOJgG GdMQI ai GdJhbjY hGdeUGObI YdjgG(B: (3Ch GdGfVeGe GdjgG dGMbG(B: (3aHbOQ eG MXjJ Hg ETcGdjI Mbhb GdEfSGf h MQjGJg GdCSGSjI ef ecGfI dOi GdeLJeY GdOhdi(B: (3h dG Tc ai Cf eLQjGJ GdYdGbGJ GdOhdjI EPG eG JaMUfGgG fLOgG dG JNdh ef GdCYeGd GdJONdjI GdJi ef NdGdgG jecf Cf ojUfa GdYed GdOhdi Cfg eTQhY Ch ZjQ eTQhY HGdQLhY ajg Edi GdTQYjI GdOhdjI h eOi JWGHbg eYgG egeG cGfJ CSGdjH gPG GdJONd(B. (3dPG ChUJ GdOQGSI HVQhQI hVY JYQja eMOO deaghe GdSde h GdCef GdOhdjjf HMjK jJe bWY GdWQjb CeGe Gdbhi GdJi JYed Ydi JhSjY eaghe gPG GdeHOC dJYWi dfaSgG ZWGA eG ddJONd ZjQ GdeTQhY ai GdTDhf GdOGNdjI ddOhd h GfJgGc SjGOJgG(B. (3VQhQI JYOjd GdeGOI (B2/7 (3ef ejKGb GdCee GdeJMOI(B: (3HMjK jJe JMOjO GdeSGFd GdJi jLhR ddefXeGJ GdOhdjI Cf JJYGed eYgG h Jdc GdJi dG jLhR dgG GdJYGed eYgG JaGOjkG dZdHI GdGYJHGQGJ GdSjGSjI Yf CYeGd eHOC GdGNJUGU GdOGNdi NGUI ef bHd GdOhd GdcHQi h GYJHGQ GdbGfhf GdOhdi gh GdeQLY GdCSGSi ai gPG GdUOOs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi, (B2021s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B214-2356s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdOhdjs; (3GdJONd GdOhdis; (3MeGjI Mbhb GdGfSGfs; (3eHOC GdSjGOIs; (3Gbdje chShaGs; (3GaZGfSJGfs; (3GdYQGbs; (3MGdGJ GdGHGMIs; (3djHjGs; (3acQI GdGef GdLeGYjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs